2023
DOI: 10.3389/fendo.2023.1094353
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of stress hyperglycemia ratio on early neurological deterioration and functional outcome after endovascular treatment in patients with acute ischemic stroke

Abstract: Background and PurposeHyperglycemia has been associated with unfavorable outcome of acute ischemic stroke, but this association has not been verified in patients with endovascular thrombectomy treatment. This study aimed to assess the impact of stress hyperglycemia ratio on early neurological deterioration and favorable outcome after thrombectomy in patients with acute ischemic stroke.MethodsStroke patients with endovascular thrombectomy in two comprehensive centers were enrolled. Early neurological deteriorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…36 Similarly, a multi-center randomized controlled trial yielded comparable results by revealing no significant difference in 90-day mortality rates among patients without preexisting diabetes who developed hyperglycemia within 24 h of admission. 37,38 Other studies have likewise supported these findings, suggesting that meticulous blood glucose management through insulin administration during stroke does not improve the outcome or reduce mortality for patients with acute ischemic stroke; instead, it appears to heighten the risk of hypoglycemia. 39 The relationship between stress-induced hyperglycemia and stroke remains inconclusive, a situation possibly arising from the subsequent factors: ① Variation in Diagnostic Criteria: A substantial disparity exists in the diagnostic criteria for stressinduced hyperglycemia across various studies.…”
Section: Discussionmentioning
confidence: 96%
“…36 Similarly, a multi-center randomized controlled trial yielded comparable results by revealing no significant difference in 90-day mortality rates among patients without preexisting diabetes who developed hyperglycemia within 24 h of admission. 37,38 Other studies have likewise supported these findings, suggesting that meticulous blood glucose management through insulin administration during stroke does not improve the outcome or reduce mortality for patients with acute ischemic stroke; instead, it appears to heighten the risk of hypoglycemia. 39 The relationship between stress-induced hyperglycemia and stroke remains inconclusive, a situation possibly arising from the subsequent factors: ① Variation in Diagnostic Criteria: A substantial disparity exists in the diagnostic criteria for stressinduced hyperglycemia across various studies.…”
Section: Discussionmentioning
confidence: 96%
“…By introducing HbA1c, the SHR, an index of relative glycemia, was developed in an effort to obtain new insights into the relationship between hyperglycemia and patient outcomes. Previous studies had demonstrated that the strong relationship between SHR and poor clinical outcomes in acute coronary syndrome ( 33 36 ), acute ischemic stroke ( 13 , 37 ), heart failure and type 2 DM ( 38 ). Our study also demonstrated the strong association between SHR and mortality in cardiac arrest patients.…”
Section: Discussionmentioning
confidence: 99%
“…This stress state can aggravate the progression of stroke disease, aggravate the damage and edema of the patient's brain tissue, expand the infarct size, and further increase disability and mortality. Stress hyperglycemia ratio (SHR) indicator considering both glucose and HbA1C to quantify this stress condition 7 . The degree of stress hyperglycemia can be accurately identified and quantified, and the predictive value of SHR is better than other indicators 8 .…”
Section: Introductionmentioning
confidence: 99%